Testing the Acoustic Silencers - PIERCHAŁA, Marek Dariusz (Archives of Acoustics, 2018)
Problems associated with designing silencers are presented. Results of direct tests of silencers for cooperation with systems of axial fans, as well as results of numerical tests of a two stage acoustic silencer, are given. The numerical tests enabled determining the distribution of acoustic field inside the silencer and in the surrounding area. In those tests A sound insertion losses for different variants of installation inside the silencer, as well as for two different types of absorbing material used to fill the silencer walls, were determined. Impact of design features of silencers on effectiveness of noise reduction is described. Also, a technical sketch of a universal silencer with significant noise reduction ($D_{ipS}$ = 39.1 dB) which can be successfully used in many ventilation systems is presented.